2009
DOI: 10.1089/gtmb.2008.0075
|View full text |Cite
|
Sign up to set email alerts
|

1q44-qter Trisomy:Clinical Report and Review of the Literature

Abstract: Subtelomeric rearrangements are one of the main causes of multiple congenital anomalies and mental retardation, and they are detected in 5% of patients. We report on a 6.5-year-old boy with mental retardation, dysmorphic features, and behavioral problems, who revealed 1q44-qter trisomy and 22q13.3-qter monosomy due to a maternal cryptic translocation t(1;22). We compared the clinical and cytogenetic data of our patient with those of another case presenting a pure 22qter monosomy and with those of all 1qter tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Patient No. 21 had a 0.61 Mb microduplication in the 1q44 region, which is related to previously reported distal 1q trisomy syndrome 9. Patient No.…”
Section: Resultssupporting
confidence: 73%
“…Patient No. 21 had a 0.61 Mb microduplication in the 1q44 region, which is related to previously reported distal 1q trisomy syndrome 9. Patient No.…”
Section: Resultssupporting
confidence: 73%
“…In this case report, we describe a cryptic chromosomal rearrangement in two cousins similarly affected with partial 9p monosomy and partial 1q trisomy, both originating from a balanced translocation t(1;9) (q44;p24.3) present in both mothers. Although monosomy 9p has been seldom reported (Swinkels et al, 2008), some cases of 1q44 duplication have been described (Lenzini et al, 2009), while reported cases with both alterations, partial monosomy 9p and partial trisomy 1q are even rarer (Verbraak et al, 1992;Kulikowski et al, 2008).…”
Section: Introductionmentioning
confidence: 99%